The Proteomic Changes in Cynara Cardunculus L. var. altilis DC Following the Etiolation Phenomena Using De Novo Sequence Analysis. (1st June 2010) - Guarino, Carmine; De Simone, Luciana; Santoro, Simona; Caira, Simonetta; Lilla, Sergio; Calabrese, Maria Grazia; Chianese, Lina; Addeo, Francesco
Abstract : Etiolation of vegetables is a complex phenomenon implying qualitative and quantitative protein changes. The 2-DE protein profile of green and etiolated fleshy stalk samples has shown great differences in the 4–7 pH and 10 to 250 kDa mass range. Currently, a shortage of Cynara DNA or protein sequences has required the use of de novo sequencing and BLAST similarity searches for protein identification. Highlighted herein is an application of proteomics to the identification of proteins, which in a great part matched those from the Viridiplantae order. Quantitative evaluation, statistical analyses, and MALDI-TOF MS characterization of the resolved spots in green and etiolated samples of C. cardunculus enabled us to identify 46 out of 60 spots, containing 21 spots included conserved Viridiplantae domains. The etiolation process is discussed in light of the identification of some proteins involved in specific biochemical and metabolic pathways.